Going solo - Dahl, Roald (London : Puffin Books, 1988)
As a young man working in East Africa for the Shell Company, Roald Dahl recounts his adventures living in the jungle and later flying a fighter plane in World War II.
6.5
Young Adult.
Young Adult
Keywords: Dahl, Roald -- Juvenile literature; Dahl, Roald; Dahl, Roald; Authors, English -- 20th century -- Biography -- Juvenile literature; World War, 1939-1945 -- Personal narratives, British -- Juvenile literature; Authors, English; World War, 1939-1945 -- Personal narratives; English authors; World War, 1939-1945 -- Personal narratives; Africa, East -- Juvenile literature; Africa, East; East Africa; Bibliographical fiction